Pediatric paragonimiasis: a retrospective analysis of cases from a county in south-west China - Jiang, Yong-xin; Li, Gong-qiang; Pan, Cheng-jing; He, Zhong-qiu; Wang, Chao; Mu, Qi-ru; Cao, Lu-lu (Frontiers in Pediatrics, 2023)
Introduction: The clinical manifestations of paragonimiasis are diverse and non-specific, and can easily lead to misdiagnosis. We aimed to analyze the clinical manifestations, laboratory features, treatment, and clinical outcome of children with paragonimiasis in order to improve recognition of this disease and avoid misdiagnosis. Methods: Children diagnosed with paragonimiasis from August 2016 to July 2022 were included in the study. Information on population informatics, medical history, and laboratory features was extracted from case data. The clinical features of paragonimiasis were retrospectively analyzed. Results: A total of 45 children were included in this study. All children had, at least, one risk factor. The clinical features mainly included fever, cough, pleural effusion, peritoneal effusion, and subcutaneous nodules. The main imaging findings were alveolar exudation, peritoneal effusion, pleural thickening, and local nodules. The “tunnel sign” finding on computed tomography (CT)/magnetic resonance imaging (MRI) was helpful in establishing the diagnosis of paragonimiasis. After praziquantel treatment, most of the children improved, and one child with cerebral paragonimiasis experienced sequelae. Conclusion: Most children with paragonimiasis have a good prognosis, but few children can experience sequelae. Avoidance of untreated water and raw food is a simple, feasible, and effective preventive measure.